2022
DOI: 10.1038/s41598-022-08578-2
|View full text |Cite
|
Sign up to set email alerts
|

Movement observation activates motor cortex in fibromyalgia patients: a fNIRS study

Abstract: Scientific evidence points to a shared neural representation between performing and observing an action. The action observation notoriously determines a modulation of the observer’s sensorimotor system, a phenomenon called Motor Resonance (MR). Fibromyalgia (FM) patients suffer from a condition characterized by generalized musculoskeletal pain in which even simple movement can exacerbate their symptoms. Maladaptive functioning of the primary motor cortex is a common finding in patients with chronic pain. Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…In FM patients, who before TDCS expressed reduced cortical metabolism during active hand movement on both hemispheres, in accordance with previous studies [ 14 , 15 ], the anodal stimulation of M1 could compensate for this functional gap, restoring the activity at least on the stimulated hemisphere. On the opposite side, slight differences persisted between patients and controls, for a reduced effect in patients and the already explained phenomenon of increased oxyhemoglobin levels in controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In FM patients, who before TDCS expressed reduced cortical metabolism during active hand movement on both hemispheres, in accordance with previous studies [ 14 , 15 ], the anodal stimulation of M1 could compensate for this functional gap, restoring the activity at least on the stimulated hemisphere. On the opposite side, slight differences persisted between patients and controls, for a reduced effect in patients and the already explained phenomenon of increased oxyhemoglobin levels in controls.…”
Section: Discussionsupporting
confidence: 91%
“…According to previous reports [ 14 ], FM patients had slower movement as compared to controls. The low motor efficiency, corresponded to a reduced metabolic activation of the cortical motor network, as also previously shown [ 14 , 15 ]. The motor impairment could be a tract of FM, due to an inhibitory effect on the motor cortex caused by chronic pain [ 32 ], or to a primary cortical motor network dysfunction, with a low efficient modulatory effect on noxious information processing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Potentially, this might be due to the unfamiliarity of participants with the exercises. A previous study has suggested that observing a familiar action activates the sensorimotor maps relative to the person’s experience, but if the viewer observes unfamiliar movements, the motor system could in turn be inhibited [ 52 ]. These might suggest that the choice of movement for mental practice might have an impact on the results.…”
Section: Discussionmentioning
confidence: 99%
“…SPM-1 within subject analysis was performed to estimate the degree of activation in each channel with respect to the baseline 31 . For group analysis of the brain activity in accordance with the statistical analysis, SPM-2 between subject analysis was used (p<0.05, corrected for multiple comparisons) 32 .…”
Section: ) Functional Near Infrared Spectroscopymentioning
confidence: 99%